The Psychological Impact of the Spiritual Experience of Drug Abuse Patients in Pondok Inabah XX Suryalaya - Muslih, Moh; Ali, Anshari P. (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The present study was aimed to describe the impact of psychological changes of spiritual experience therapy among drug abuse patients in Pondok Inabah XX Suryalaya. The present study was a field study with phenomenological-psychological approach on drug abuse patients. Data was collected through in-depth interview with drug abuse patients and counselors to observe any psychological change. Observation was used to explore the patients’ attitude change through notes of emotional changes during therapy on drug abuse patients. Meanwhile, the data analysis technique was inductive analysis with going, simultaneous, and cyclical processes. The research result showed that the psychological conditions of drug abuse patients before the therapy showed emotional disorders, e.g. aggressiveness, anger, sadness, disappointment, pessimism, and disheveled and dirty physical condition. After the patients underwent spiritual experience, they had positive psychological conditions, e.g. feeling close to God, calm, comfortable, happy, and optimistic, wanting to be successful, wanting to make their parents happy, and regretting being addicted to drugs.